2009
DOI: 10.1002/hyp.7453
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between a saline lagoon and a semi‐confined aquifer on a salinized floodplain of the lower River Murray, southeastern Australia

Abstract: Abstract:The transport of saline groundwater from local and regional aquifers to the lower River Murray in South Australia is thought to be greatly influenced by the incised lagoons and wetlands that are present in the adjacent floodplain. Interactions between a saline lagoon and semi-confined aquifer at a floodplain on the River Murray were studied over a 1-year period using hydrogeological techniques and environmental tracers (Cl , υ 2 H and υ 18 O). Piezometric surface monitoring showed that the lagoon acte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…These extraordinarily elevated isotopic compositions may represent evaporation under very low humidity conditions (I. Cartwright, pers comm;Banks et al, 2009;Cartwright, Hall, Tweed, & Leblanc, 2009;Tweed, Leblanc, Cartwright, Favreau, & Leduc, 2011). We test this hypothesis by modelling the evaporation process as described below.…”
Section: Isotope Geochemistrymentioning
confidence: 99%
“…These extraordinarily elevated isotopic compositions may represent evaporation under very low humidity conditions (I. Cartwright, pers comm;Banks et al, 2009;Cartwright, Hall, Tweed, & Leblanc, 2009;Tweed, Leblanc, Cartwright, Favreau, & Leduc, 2011). We test this hypothesis by modelling the evaporation process as described below.…”
Section: Isotope Geochemistrymentioning
confidence: 99%
“…Banks et al (2009) studied the role of a floodplain wetland in modifying groundwater-surface water interactions between a floodplain aquifer and the River Murray. They found that the wetland intercepted groundwater discharge from a nearby irrigated upland area, concentrated it by evaporation and then recharged more saline water to the floodplain aquifer.…”
mentioning
confidence: 99%